Sistem Penulangan pada Karakter 3D dalam Film Animasi The Relativity Of Reality - Abdulah Rosyidouddin El Islami; Charles De Haan (Lembaga Pengembangan Kinerja Dosen, 2025)
Digital animation technology is increasingly advancing, as evidenced by the proliferation of animated films worldwide. This is also true in Indonesia, where the production of animated films has increased significantly due to the improvement and ease of digital animation technology. One of the most important parts of the animation process is the rigging process, which involves creating a skeleton for the character or object so that it can move and appear lifelike. The rigging process in the short animated film